Looking at the forest from below: the role of seedling root traits in the adaptation to climate change of two Nothofagus species in Argentina - Duboscq Carra, Virginia Gisela; Letourneau, Federico Jorge; Pastorino, Mario Juan (2018)
Global climate change (CC) is an evolutionary challenge for natural tree populations. Scientific experts forecast an increase in temperature and a decrease in precipitation in the Argentine Patagonian Cordillera. Knowledge of the variation of adaptive traits at the seedling stage is crucial to prediction the adaptability of forest tree species. We aim to analyze genetic variation in root and shoot quantitative traits among and within natural populations of two key North Patagonian forest species, in order to evaluate their ability to deal with CC through adaptation. We established two common garden nursery trials: (1) 81 open pollinated families of Nothofagus obliqua from eight natural populations, and (2) 74 families of Nothofagus alpina from seven populations. At the end of the first growing season we measured shoot height, diameter, root length and root and stem dry biomass; we also estimated foliage biomass. In addition the root to stem ratio, specific root length and the root to shoot ratio were calculated. For both species intra-population variation was generally low, and average differentiation was moderate, with high levels of differentiation in some traits related to drought stress, indicating low adaptation capacity but also adaptation to current stressful conditions, which means it may be possible for some populations to survive CC without changing their genetic structures. Further studies are needed, including phenotypic plasticity assays, to complete the picture.